Investigating the impact of standardized fertigation on soil chemical properties, nutrient content and total nutrient uptake in garlic crop (Allium sativum. L) - RATTAN, VARSHA; SPEHIA, R.S. (Journal of Soil and Water Conservation, 2024)
An experiment conducted at the Experimental Farm of the Department of Soil Science and Water Management, Dr. Y.S. Parmar University of Horticulture and Forestry, Solan, HP in the year 2018-19. This study aimed to examine the effects of fertigation levels and mulching on soil properties, nutrient content in garlic leaves and bulbs, and nutrient uptake. The experiment used a randomized block design with eight treatments, replicated three times. Results demonstrated no significant differences in soil pH, EC, and organic carbon. The treatment F1M1 (fertigation at 100% RDF via water-soluble fertilizer + polyethylene mulch) showed the highest available N (379.48 kg ha-1and 408.33 kg ha-1), P (90.60 kg ha-1 and 76.15 kg ha-1), K (365.19 kg ha-1and 359.50 kg ha-1) in the 0-15 cm and 15-30 cm depths, respectively. Similarly, F1M1 yielded the maximum nutrient content in garlic leaves and bulbs. The greatest nutrient uptake of N (44.35 kg ha-1), P (14.16 kg ha-1), and K (59.91 kg ha-1) was observed in F1M1, while S uptake was highest in F1M0 (18.86 kg ha-1), nearly equivalent to F1M1 (17.64 kg ha 1). Hence, fertigation at 100% RDF through water-soluble fertilizer proved superior, followed by 80% RDF through the same fertilizer type.